Penggunaan Aplikasi Permainan di Smartphone dalam Pemberian Promosi Kesehatan Mengenai Diet Sehat Pada Anak : Tinjauan Literatur - Utami, Ayu Fitria (Universitas Tanjungpura, 2019)
The Using of Game Application in Smartphone for Giving Health Promotion about Healthy Diet In Children : Literature Review. Obesity is a phenomenon which has increased prevalence in children. In 2016, There are 340 million children in age 5-19 years old have obesity in worldwide and 8 from 10 children in Indonesia have obesity as well. Obesity in children leads to some health problems such as Hipertention, High Cholesterol, and Diabetes Mellitus Type II. These cases can be happen if children have no good diet. Healthy diet is influenced by parents and children